UNFSS Science Days Side Event: Gender equality, women’s empowerment, and food systems - International Food Policy Research Institute; Self Employed Women’s Association (SEWA) (International Food Policy Research Institute, 2021)
The UNFSS Side Event on Gender Equality, Women’s Empowerment, and Food Systems underscored the importance of addressing gender equality to transform food systems. While there is a broad consensus in the literature about how to improve gender equality and women’s empowerment in food systems, there is little evidence on causal pathways or processes. This side event presented evidence from a new review of evidence on gender equality, women’s empowerment, and food systems. Dr. Jemimah Njuki, Director for Africa, IFPRI, presented the findings from the review. The presentation of findings was followed by a panel discussion with Steve Cole, Senior Scientist, Gender Specialist, International Institute for Tropical Agriculture, Corinna Hawkes, Director, Centre for Food at City, University of London, and Reema Nanavaty, Self Employed Women’s Association, where the discussants provided key insights on pathways mentioned in the review, practical approaches to addressing gender inequality in food systems, comments on the recommendations provided by the review, and future action steps for the advancement of the results found in the review. Dr. Ruth Meinzen-Dick, Senior Research Fellow, IFPRI, provided closing remarks.